Pemahaman Hadis Keutamaan Alī Ibn Abī Ṭālib Dalam Pandangan Syiah - Nabilah, Jauharatu (UIN Sunan Kalijaga Yogyakarta, 2022)
This study examines the methodology of understanding the hadith used by the Shia in interpreting the hadith about the primacy of Alī Ibn Ab Tālib as the high priest of the Shia. This methodology of understanding hadith becomes very important to study because it has major implications for the building of Shia theology, especially if it is associated with the division of them into at least four sects. In its application, this research applies a systematic approach which is defined as a system of thinking in which Shia understandings of a hadith are systematically and logically constructed in an epistemological system of thinking. This analysis process begins with describing, studying and interpreting the data obtained from Shia origin sources which are then processed and ultimately produce a conclusion. From this research, the writer concludes that the Shia are not completely complete and comprehensive in understanding the context of a hadith. This is evidenced by the existence of several distinctions that cause the interpretation of the hadith about the virtues of Ali Ibn Ab ālib may have exceeded the intended purpose of the Prophet.